Kontribusi Supervisi Kepala Madrasah dan Motivasi Kerja Guru terhadap Kinerja Mengajar - Taufik Effendi; Ifnaldi Ifnaldi; Murni Yanto; Jumira Warlizasusi (Alignment:Journal of Administration and Educational Management, 2020)
The purpose of this study was to determine the contribution of madrasah head supervision and teacher work motivation to teacher performance. This research uses quantitative methods, with data collection techniques using questionnaires, documentation and interviews, then data analysis techniques using correlational. The results of the study, the correlation coefficient between the supervision activity variable (X1) with the performance variable (Y) is 0.501 and the correlation coefficient between the motivation variable (X2) and the performance variable (Y) is 0.493, each greater than the value of r table in n 38 which is 0.325. Thus the three variables are positively correlated. In conclusion, there is a relationship between the contribution of madrasah head supervision and teacher work motivation on teacher teaching performance. Keywords: Supervision of Madrasah Head, Work Motivation, Teaching Performance